Sunflower seed byproduct and its fractions for food application: An attempt to improve the sustainability of the oil process - de Oliveira Filho, Josemar Gonçalves [UNESP]; Egea, Mariana Buranelo (Wiley, 2021)
Abstract: The sunflower (Helianthus annus L.) is one of the main oil crops in the world grown for the production of edible and biodiesel oil. Byproducts of the extraction of sunflower oil constitute a raw material with potential for several applications in the food area due to its chemical composition, including the high content of proteins and phenolic compounds. Thoughtful of a consumer increasingly concerned with the environmental impact, we try to clarify in this review the potential of using sunflower seed byproducts and their fractions to enhance the production of potentially functional foods. The applications of sunflower seed byproduct include its transformation into flours/ingredients that are capable of improving the nutritional and functional value of foods. In addition, the protein isolates obtained from sunflower seed byproduct have good technological properties and improve the nutritional value of food products. These protein isolates can be used to obtain protein hydrolysates with technological and bioactive properties and as matrices for the development of edible, biodegradable, and active films for food. The sunflower seed byproduct is also a source of phenolic compounds with bioactive properties, mainly chlorogenic acid, which can be extracted by different methods and applied in the development of functional foods and active and bioactive food packaging. The use of sunflower seed byproduct and its fractions are promising ingredients for the development of healthier and less expensive foods as well as the alternative to decrease the environmental problems caused by the sunflower oil industry.
Keywords: bioactive peptides; functional foods; phenolic compounds; sunflower meal